2021
DOI: 10.17051/ilkonline.2021.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Blended learning innovation of social media based active English during the COVID-19 pandemic

Abstract: This study aims to describe the implementation of blended learning innovation of social mediabased (sosmed-based) English teaching in improving students' active English skill during the Covid19 Pandemic. The innovation was made by implementing the Communicative Approach which integrated elearning platforms including Be-Smart, Zoom, and Google Classroom with social media (YouTube, Instagram, Facebook). The indicators of active English skill are: students' activeness, self-confidence, and creativity and innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(31 reference statements)
0
7
0
1
Order By: Relevance
“…In this regard, for the speaking skill to develop in emergency online teaching, synchronous online discussion sessions with proper task negotiation, task planning and other teaching methods such as question and answer sessions was reported to increase students' speaking skills (Rinekso & Muslim, 2020). Also, social media-based blended teaching contributed positively to improving the active English skills of the students during the pandemic (Mustadi et al, 2021).…”
Section: Findings Of the Second Research Question Based On The Impact Of Covid-19 On English Language Teaching And Learning From The Globmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, for the speaking skill to develop in emergency online teaching, synchronous online discussion sessions with proper task negotiation, task planning and other teaching methods such as question and answer sessions was reported to increase students' speaking skills (Rinekso & Muslim, 2020). Also, social media-based blended teaching contributed positively to improving the active English skills of the students during the pandemic (Mustadi et al, 2021).…”
Section: Findings Of the Second Research Question Based On The Impact Of Covid-19 On English Language Teaching And Learning From The Globmentioning
confidence: 99%
“…The interactive course environment improved not only their language skills but also their ICT skills (Aji et al, 2020;Rahman, 2020). The students' tendency to adapt to online learning was also enhanced by social media; this helped to focus the online learning community, in which they reproduced linguistic content by making use of free online resources and were involved in social interaction with their peers and teachers (Krishan et al, 2020;Mustadi et al, 2021). It was also reported that another aspect the students regarded positively is that online learning was appropriate for visually-impaired students, who were learning English remotely at home (Hamid, 2020).…”
Section: Findings Of the Third Research Question Based On The Attitudes And Motivations Of Teachers And Students Towards Emergency Onlinementioning
confidence: 99%
“…AI provides personalized learning experiences, adapts to students' needs, and offers instant feedback . It enhances accessibility, making language learning available to a wider audience (Mustadi, Annisa, & Mursidi, 2021). AI can also analyze vast amounts of data to identify trends and areas where students struggle (Gruber, Matt, & Leier, 2023).…”
Section: Ai Integration In Language Educationmentioning
confidence: 99%
“…As indicated in this study and as research in the field proves, a lot of students at the tertiary level usually prefer to watch popular American TV serials or soap operas as they are shorter than a movie. Needless to say, media that can be exploited as an audiovisual instructional material reflect real-life situations in which the real language is used in contextualized settings (Mustadi, Annisa, & Mursidi, 2021;Tomlinson, 2019;Wu, Lin, Marek, & Ou Yang, 2021).…”
Section: Game Of Thronesmentioning
confidence: 99%